ANALISIS PENGARUH EASY OF USE, QUALITY OF INFORMATION TERHADAP TRUST DAN REPURCHASE INTENTION E-TICKET PADA APLIKASI TRAVELOKA - Gunarso Wiwoho (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
The purpose of this study is to analyze the effect of easy of use, quality of information on trust, and repurchase intention e-ticket on the Traveloka application in Kebumen Regency. The study was conducted using populations originating from people living in Kebumen Regency and had transacted using Traveloka with a sample size of 100 respondents. The analytical method used in this study consisted of descriptive and quantitative analysis with the type of determination of respondents through purposive sampling. Analysis carried out through quantitative methods is the validity test, reliability test, classical assumption testing, t-test, determination coefficient test, path analysis, and Sobel test. The results showed that based on the validity and reliability tests all variables were declared valid and reliable. Based on the t-test the easy of use variable significantly affects trust, quality of information significantly influences trust, easy of use significantly influences repurchase intention, quality of information, and trust has an effect on repurchase intention. The Sobel test shows that trust cannot mediate easy of use with repurchase intention and trust can mediate the quality of information with repurchase intention.